Sexual transmission of Toxoplasma gondii in sheep - Lopes, Welber Daniel Zanetti [UNESP]; Rodriguez, Joana D'Ark [UNESP]; Souza, Fernando A. [UNESP]; dos Santos, Thais Rabelo [UNESP]; dos Santos, Ricardo Silva [UNESP]; Rosanese, Walter Matheus [UNESP]; Lopes, Werik Renato Zanetti [UNESP]; Sakamoto, Cláudio Alessandro [UNESP]; da Costa, Alvimar José [UNESP] (Elsevier, 2013)
Male sheep of reproductive age were distributed into three groups: GI, a sheep inoculated (oral) with 2.0×105 oocysts of the P strain of Toxoplasma gondii; GII, a sheep infected (subcutaneous) with 1.0×106 tachyzoites of the RH strain of T. gondii; and GIII, a sheep kept as a control (not infected). After the inoculation of the males, 12 breeding ewes, which were not pregnant and which were serologically negative for reproductive diseases (particularly toxoplasmosis), were distributed into three groups, synchronized, and subsequently exposed to natural mating with previously inoculated males. The distribution was as follows: five ewes that underwent natural mating with the GI male, five ewes that were exposed to natural mating with the GII male, and two ewes that were mated with the non-infected male (control). Serum samples of all the ewes were collected on days -30, -14, -7, -1, and 0 (days before natural mating) and on days 1, 3, 5, 7, 11, 14, and weekly until birth; the presence of serum antibodies against T. gondii was assessed by IFAT. Using a bioassay and PCR, T. gondii was isolated from the semen of the infected reproducing sheep before mating. Following natural mating, 5 of the 12 females displayed antibodies specific for T. gondii; of these animals, two of the ewes underwent natural mating with the male inoculated with oocysts (GI) and three with the male infected with tachyzoites (GII). One of the females that displayed antibodies specific to this coccidian and that underwent natural mating with the GII sheep had a macerated fetus on the 70th day following coverage. Using a bioassay after the birth, it was possible to isolate T. gondii from samples of the pool of tissues from the five females that seroconverted after natural mating and from their respective lambs. Using PCR, the DNA of T. gondii was isolated from the pool of tissues from one and two females exposed to natural mating with the reproductive males infected with the oocysts and tachyzoites, respectively. Using this technique, it was also possible to diagnose the presence of the parasite in the pool of tissues from the lambs of one female that underwent natural mating with the male sheep infected with oocysts. These results demonstrated the sexual transmission of T. gondii in the sheep species with consequent vertical transmission to their lambs. © 2013 Elsevier B.V.
Keywords: Ovine; Semen; Sexual transmission; Toxoplasma gondii; DNA; parasite antibody; toxoplasma gondii antibody; Toxoplasma gondii DNA; unclassified drug; animal cell; animal experiment; animal tissue; antibody specificity; birth; breeding line; Coccidia; controlled study; DNA isolation; ewe; female; genital tract infection; inoculation; lamb; male; mating; nonhuman; oocyst; parasite isolation; parasite transmission; seroconversion; sexual transmission; sexually transmitted disease; sheep disease; sperm; subcutaneous tissue; tachyzoite; tissue section; toxoplasmosis; Animalia; Ovis; Ovis aries